Antibacterial Activity of Combination of Ethanol Extract of Pepermine Leaves (Mentha piperita L.) and Amikacin Against Klebsiella pneumonia, Staphylococcus aureus, and Escherichia coli - Peni Indrayudha (Journal of Nutraceuticals and Herbal Medicine, 2021)
Peppermint leaves have been known to have antibacterial and antifungal activity. Amikacin is a semisynthetic derivative of kanamycin which is active against both Gram-positive and Gram-negative enteric bacteria. The combination of plant extracts with antibiotics is one way or alternative to overcome bacterial resistance to antibiotics. The purpose of this study was to determine the combined effect of the ethanolic extract of peppermint (Mentha piperita L.) and amikacin against Klebsiella pneumonia, Staphylococcus aureus, and Escherichia coli as well as the compounds contained in the ethanolic extract of peppermint (Mentha piperita L.) leaves. Antibacterial activity was tested using the disk diffusion method (Kirby Bauer) and the phytochemical screening test using the tube test method. The concentration of peppermint leaf ethanol extract for the combination test was 200 mg/mL and 400 mg/mL, for the concentration of amikacin used was 5 mg/mL with three comparisons made, namely 25:75, 50:50, and 75:25. The results showed a synergistic effect with the largest inhibition zone diameter at a ratio of 25:75 at a concentration of 200 mg/mL, which was 36.25±2.5 mm on Klebsiella pneumonia bacteria. While at a concentration of 400 mg/mL the diameter of the largest inhibition zone was 40±1.63 mm in Klebsiella pneumoniae bacteria with a ratio of 75:25. The results of statistical tests using the t-test showed a significance value of 0.000 0.05 so that there was a significant difference in the administration of each concentration to the resulting inhibition zone. The results of the phytochemical screening test contained alkaloids, phenolic compounds, flavonoids, tannins.